Antiviral and antiretroviral drug shortages amidst COVID-19: How Africa is struggling - Sudhan Rackimuthu; Zohra Kazmi; Osman Kamal Osman Elmahi; Reem Hunain; Behram Khan Ghazi; Zain Ali Zaidi; Ana Carla dos Santos Costa; Shoaib Ahmad; Mohammad Yasir Essar (University of Minnesota Libraries Publishing, 2021)
Antiviral drugs are of paramount importance in the accomplishment of the vision of zero new cases of COVID-19 globally, through sustainable retaliation against viral diseases. However, several challenges currently exist in Africa which include insufficient infrastructure, deteriorating health systems, and rising costs of healthcare delivery with concomitant rising inequity with regards to access to health services amid the COVID-19 pandemic. The pandemic itself has stimulated an increased use of phytotherapy in Africa as a result of essential drug shortages that have been attributed to a plethora of contributing factors such as travel restrictions, reduced per capita income as well as increased expenditure on transport. As a result, the paucity of antiviral along with antiretroviral drugs used to combat COVID-19 as well as several other endemic viral diseases in Africa has created a worrisome state. This article therefore discusses and aims to underscore the causes, effects, and implications of antiviral and antiretroviral shortages amid COVID-19 in Africa.